Visual Basic in Easy Steps, 6th Edition Updated for Visual Basic/Studio Community 2019. - McGrath, Mike (In Easy Steps Ser., 2019)
Create Windows applications using the latest free Visual Basic/Studio Community 2017 programming environment.